2018
DOI: 10.1104/pp.18.00604
|View full text |Cite
|
Sign up to set email alerts
|

Nodulin Intrinsic Protein 7;1 Is a Tapetal Boric Acid Channel Involved in Pollen Cell Wall Formation

Abstract: Boron is an essential plant micronutrient that plays a structural role in the rhamnogalacturonan II component of the pectic cell wall. To prevent boron deficiency under limiting conditions, its uptake, distribution, and homeostasis are mediated by boric acid transporters and channel proteins. Among the membrane channels that facilitate boric acid uptake are the type II nodulin intrinsic protein (NIP) subfamily of aquaporin-like proteins. Arabidopsis (Arabidopsis thaliana) possesses three NIP II genes (NIP5;1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 84 publications
1
27
0
Order By: Relevance
“…This cooperative system ensures root B uptake, B rootto-shoot translocation and B loading into specific cells, tissues or the apoplast of different model and crop plant species (Takano et al, 2006;Miwa et al, 2007;Reid, 2007;Sutton et al, 2007;Tanaka et al, 2008;Kajikawa et al, 2011;Miwa et al, 2013;Chatterjee et al, 2014Chatterjee et al, , 2017Durbak et al, 2014;Hanaoka et al, 2014;Pallotta et al, 2014;Hua et al, 2016a;Routray et al, 2018;Shao et al, 2018). Additionally, BORs and NIPs have been demonstrated to be decisive factors determining plant B toxicity tolerance (Miwa and Fujiwara, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This cooperative system ensures root B uptake, B rootto-shoot translocation and B loading into specific cells, tissues or the apoplast of different model and crop plant species (Takano et al, 2006;Miwa et al, 2007;Reid, 2007;Sutton et al, 2007;Tanaka et al, 2008;Kajikawa et al, 2011;Miwa et al, 2013;Chatterjee et al, 2014Chatterjee et al, , 2017Durbak et al, 2014;Hanaoka et al, 2014;Pallotta et al, 2014;Hua et al, 2016a;Routray et al, 2018;Shao et al, 2018). Additionally, BORs and NIPs have been demonstrated to be decisive factors determining plant B toxicity tolerance (Miwa and Fujiwara, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Flowers are singular organs representing the last developmental phases; therefore, it is not surprising that efforts should be made to understand flower development and the roles B plays in this process, which is an exciting yet understudied field of plant biology. It has been demonstrated that NIP7;1, a facilitator of boric acid transport, is predominantly expressed in young flower anthers in a narrow developmental window ( Routray et al, 2018 ). Accordingly, nip7;1 mutants exhibit several defects in reproductive structures ( Routray et al, 2018 ), indicating that proper control of B homoeostasis in both meristem and reproductive organs is critical for the biological success of vascular plants.…”
Section: Boron Mediating Developmental Transitions In Both Shoots Andmentioning
confidence: 99%
“…It has been demonstrated that NIP7;1, a facilitator of boric acid transport, is predominantly expressed in young flower anthers in a narrow developmental window ( Routray et al, 2018 ). Accordingly, nip7;1 mutants exhibit several defects in reproductive structures ( Routray et al, 2018 ), indicating that proper control of B homoeostasis in both meristem and reproductive organs is critical for the biological success of vascular plants. Thus, this evidence suggests that obtaining and maintaining an optimal B level in flower-related tissues is often imperative for successful plant reproduction.…”
Section: Boron Mediating Developmental Transitions In Both Shoots Andmentioning
confidence: 99%
“…Contrastingly, NIP6;1, which is mainly expressed in stems, is impermeable to water and is responsible for distribution of B in the growing shoot tissues [87]. NIP7;1, with strong expression in floral tissues, seems to favor B-transport to the developing tapetal tissue of developing anthers [88].…”
Section: Elements With Only a +3 Oxidation State: Boron And Aluminummentioning
confidence: 99%